T lymphocyte heterogeneity in NSCLC: implications for biomarker development and therapeutic innovation - Liu, Yu; Qin, Denghui; Fu, Jiejun (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) immunotherapy has been revolutionized by immune checkpoint inhibitors (ICIs), yet response heterogeneity persists due to dynamic tumor-immune interactions. This review summarizes recent studies in understanding tumor-infiltrating lymphocyte (TIL) biology, highlighting CD8+ cytotoxic T cells and regulatory T cells (Tregs) as pivotal regulators of immune surveillance and suppression. We summarize emerging biomarkers such as TCR clonality, spatial distribution of tumor-infiltrating lymphocytes (TILs), and exhaustion markers including PD-1, TCF1, and TIM-3, which predict immune checkpoint inhibitor (ICI) efficacy beyond PD-L1 expression. This review specifically describes radiotherapy-induced immunogenic remodeling and peripheral T cell dynamics as innovative strategies to monitor immune response and resistance mechanisms. By integrating results from single-cell omics and AI-driven spatial analysis, we propose multidimensional frameworks of TIL in NSCLC to overcome resistance and optimize immunotherapy combinations. These insights collectively advance NSCLC immunotherapy toward precision modulation of the tumor immune microenvironment.